Distribution characteristics of tropical cyclones affecting the Vietnam region during 1992–2022 - Pham , Thi Thanh Hoa; Nguyen, Ba Thuy; Nguyen, Van Huong; Mai, Van Khiem (Vietnam Journal of Marine Science and Technology, 2024)
This research investigates the distribution characteristics of tropical cyclones affecting the Vietnam region, including the mainland and the East Vietnam Sea, from 1992 to 2022. The tropical cyclone activity showed an increasing trend, mainly in the numbers of tropical depressions and typhoons with the sustained maximum wind speed ranging from level 12 to 15 on the Beaufort Wind Scale; however, this trend did not meet the statistical 99% confidence level. The number of tropical cyclones directly affecting the mainland of Vietnam accounted for approximately 32%. Over the East Vietnam Sea, tropical cyclones presented a peak in September and a slump in February. Occurrence frequencies and probabilities were significantly high over the in-shore and off-shore regions from Quang Ninh to Phu Yen, over the North and Center of East Vietnam Sea, where the maximum frequencies could be 0.9 tropical cyclone/year over the Gulf of Tonkin higher than 1.1 tropical cyclone/year passing a grid of 1o longitude-latitude over the north East Vietnam Sea. Meanwhile, the southern offshore areas from Phu Yen - Ca Mau, Ca Mau - Kien Giang, and Thailand Gulf were less influenced by tropical cyclones. The frequency and probability of typhoons were below 0.1 tropical cyclone/year and 0.2%, respectively.